Políticas públicas na faixa de fronteira do Brasil: PDFF, CDIF e as políticas de segurança e defesa - Camilo Pereira Carneiro Filho; Lisa Belmiro Camara (Confins)
At the beginning of the 21st century, within a context of global regionalization, Brazil started to have a new policy for its border areas. With the Lula da Silva government, a major change began on Brazil's relations with its South American neighbors. The Brazilian government started to attribute to the border strip a strategic function within the framework of South American integration. The strategy was based on the implantation of infrastructures in borders zones, whose impact materializes more properly, in the twin cities located in the international limit. These works were part of IIRSA's project portfolio, an initiative created in 2000, considered a milestone in the integration of the subcontinent. From 2005 (with the research of the Retis Group /UFRJ) and 2009 (with the PDFF) the Brazilian government promoted, for the first time in the history of the country, the creation of a database that potentiated the planning and the management of the border zone. In 2010 the objectives of the PDFF would eventually be incorporated into the CDIF. Despite the greater focus given to Brazilian borders, it can be seen that there is a lack of continuity on the projects, which still suffer from the low interaction between the government agencies involved in border management. The present work seeks to bring an analysis of public policies for the border zone, implemented from the 21st century, from the perspective of International Relations.